Second-Grade Students’ Achievement and Engagement in Inquiry-Based Learning: An Exploratory Study - Winters, Jeremy; Schrodt, Katie M.; Huddleston, Tracey (FKIP-Universitas Riau, 2024)
This exploratory study examined 3 second-grade classrooms in the southeast United States. The purpose was to determine the effects and feasibility of implementing various levels of inquiry-based instruction. The study used structured, guided, and open inquiry in the project. The central content focus was on mimicry using a unit of study around pill bugs. This article reports on the unit that was implemented, results of the implementation, and implications for teachers desiring to implement inquiry-based instruction into the classroom.